2017
DOI: 10.2147/tacg.s144383
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of amplification refractory mutation system (ARMS) technique for quick and accurate prenatal gene diagnosis of <em>CHM</em> variant in choroideremia

Abstract: Choroideremia is a rare X-linked recessive inherited disorder that causes chorioretinal dystrophy leading to visual impairment in its early stages which finally causes total blindness in the affected person. It is caused due to mutations in the CHM gene. In this study, we have recruited a pedigree with choroideremia and detected a nonsense variant (c.C799T:p.R267X) in CHM of the proband (I:1). Different primer sets for amplification refractory mutation system (ARMS) were designed and PCR conditions were optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
5
0
1
Order By: Relevance
“…Regarding this report and previous studies, essentially retinopathological investigations were driven by mutational data analysis from new molecular based diagnosis, such as NGS panel covering [23]. Furthermore, we proposed that macular progressive depigmentation with pigment clumping and atrophy is seen as a major complement in the proband, which was extremely apparent in the macula.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Regarding this report and previous studies, essentially retinopathological investigations were driven by mutational data analysis from new molecular based diagnosis, such as NGS panel covering [23]. Furthermore, we proposed that macular progressive depigmentation with pigment clumping and atrophy is seen as a major complement in the proband, which was extremely apparent in the macula.…”
Section: Discussionmentioning
confidence: 78%
“…Eventually, all the detected variants of NGS in the present study were confirmed by PCR amplification and conventional Sanger-based sequencing (3500DX ABI genetic analyzer, Foster City, U.S.A.) in the proband and his family members [23–25]. In this regard, the locus-specific primers for variant verification and co-segregation analysis were designed using online Primer3 program.…”
Section: Methodsmentioning
confidence: 74%
“…Genomic DNA (gDNA) from peripheral leucocytes was extracted using a previously described phenol/chloroform method15 16 with DNA concentrations measured using a NanoDrop 2000 spectrophotometer 17. DNA was also extracted from samples of 100 individuals recruited as normal controls.…”
Section: Materials and Methods ‎mentioning
confidence: 99%
“…В 2017 году L. Yang и соавт. разработали систему праймеров amplification refractory mutation system (ARMS) для быстрой и точной пренатальной диагностики хороидеремии методом полимеразной цепной реакции (ПЦР) [23].…”
Section: клинический случайunclassified